2012
DOI: 10.5897/ajb12.2665
|View full text |Cite
|
Sign up to set email alerts
|

Combined protective effect of vitamins C and E on cadmium induced oxidative liver injury in rats

Abstract: Our study pertains to the potential ability of vitamin C and/or vitamin E, used as nutritional supplements, to alleviate oxidative stress induced by cadmium. Male rats were randomly divided into five groups of eight each. Group I served as the controls; group II received in their drinking water CdCl 2 (200 mg/L); group III received both CdCl 2 and vitamin C (1.5 g/L of water); group IV was treated with CdCl 2 and vitamin E (400 mg/kg diet); and group V received CdCl 2 + vitamin C + vitamin E. The exposure of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…The ability of these compounds to act as FR and ROS scavengers is well-established and they are widely used in the prevention of many oxidative stress-related diseases such as cancer or atherosclerosis (Padayatty et al, 2003;WHO, 2003). Moreover, numerous studies in animal models confirm the protective effect of supplementation with vitamins C and E against damage to the liver caused by heavy metals (Brzóska, Borowska, & Tomczyk, 2016;El-Refaiy & Eissa, 2013;El-Sayed et al, 2016;Greń et al, 2012;Grosicki, 2004;Layachi & Kechrid, 2012;Nemmiche, Chabane-Sari, & Guiraud, 2007).…”
Section: Vitaminsmentioning
confidence: 93%
See 2 more Smart Citations
“…The ability of these compounds to act as FR and ROS scavengers is well-established and they are widely used in the prevention of many oxidative stress-related diseases such as cancer or atherosclerosis (Padayatty et al, 2003;WHO, 2003). Moreover, numerous studies in animal models confirm the protective effect of supplementation with vitamins C and E against damage to the liver caused by heavy metals (Brzóska, Borowska, & Tomczyk, 2016;El-Refaiy & Eissa, 2013;El-Sayed et al, 2016;Greń et al, 2012;Grosicki, 2004;Layachi & Kechrid, 2012;Nemmiche, Chabane-Sari, & Guiraud, 2007).…”
Section: Vitaminsmentioning
confidence: 93%
“…Vitamin E partially prevented this metal-caused increase in the concentrations of PC and MDA, and inhibition of the activities of CAT and SOD. Moreover, vitamin E attenuated this element-induced decrease in the hepatic concentration of GSH and decreased the activity of LDH in the liver to a value lower than in the control group(Nemmiche et al, 2007) Layachi and Kechrid (2012). have shown that supplementation with vitamins C and E together was more effective in the protection from the adverse effects of Cd in this organ than administration of these vitamins separately.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Les lots 2, 3, 4, 5 et 6 de chaque sexe ont reçu par gavage respectivement 1/50 ième , 1/40 ième , 1/30 ième , soit1/20 ième et 1/10 ième de la DL 50 (200 mg/kg pc) de la solution de sulfate de cadmium qui sont respectivement 4; 5; 6,66 ; 10 et 20 mg/kg de poids corporel (pc). La durée de traitement des rats au sulfate de cadmium était de 30 Jours (Layachi et Kechrid, 2012). Et le volume administré était de 1ml par jour chaque matin pendant la durée de traitement.…”
Section: Méthodeunclassified
“…In the treatment of these heavy metal-related intoxications, the use of a chelator for the chelation of the metals passing into the systemic circulation is often preferred (Flora, Mittal, & Mehta, 2008;Tandon et al, 2003;Xu et al, 1996). However, many antioxidant substances which are applied in order to prevent the possible liver oxidative stress are investigated within the scope of previous studies (Eşrefoglu, Gül, Dogru, Dogru, & Yürekli, 2007;García-Niño & Pedraza-Chaverrí, 2014;Layachi & Kechrid, 2012;Zafeer, Waseem, Chaudhary, & Parvez, 2012). Diosmin is also one of the known antioxidants (Firuzi et al, 2011;Pietta, 2000).…”
mentioning
confidence: 99%